Implementation of learning guidance services with brainstorming techniques in preventing learning difficulties of students of state senior high school 1 Bandar Lampung - Monica, Mega Aria; Asri Ulhusna (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
This research is entitled "Implementation of Tutoring Services Using Brainstorming Techniques in Preventing Learning Difficulties for Students at SMA Negeri 1 Bandar Lampung". Learning difficulties are a condition that causes students not to be able to learn as they should, resulting in low learning achievement. Students who experience problems with their learning are usually characterized by symptoms such as low learning achievement, low learning motivation, lack of interest in students following lessons, and low interest or enthusiasm for learning.The problem in this research is how to implement tutoring services using brainstorming techniques to prevent students' learning difficulties at SMA Negeri 1 Bandar Lampung. Apart from that, this research aims to determine the stages of implementing tutoring services using brainstorming techniques at SMA Negeri 1 Bandar Lampung. This research uses a qualitative descriptive method. Data collected used observation, interview, and documentation methods involving resource persons, namely guidance and counseling teachers and several students. The results of this research state that after guidance and counseling teachers have provided tutoring services using brainstorming techniques effectively, students slowly change, showing positive things such as starting to do assignments little by little, beginning to take part in learning activities, there is motivation and enthusiasm for learning in class. Actively ask the teacher if there is an assignment or material that is difficult to understand.